Análise da teoria de Winnicott sobre o fenômeno da regressão no contexto analítico - Drudi, Alec (Universidade Federal de São Carlos, 2023)
The present work aims to study the concept of regression within the theory formulated by Winnicott, following a path from the emotional development theory and the consequences of environmental failures, until reaching a relation with the phenomenon of regression, bringing practical cases from the author, in order to observe how this mechanism can arise, in different analytical contexts.
Analysis of Winnicott's theory on the phenomenon of regression in the analytical context
Keywords: Regressão; Winnicott; Trauma; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA